State of knowledge of bryology and ethnobryology in Ecuador: A systematic review for three decades (1990–2025) - Benítez, Ángel; Yangua-Solano, Erika; Vega, Marlon (Ethnobotany Research and Applications, 2026)
Background: Bryophytes are a highly diverse group, with approximately 23,000 species worldwide and about 1,650 species recorded in Ecuador, playing key roles in biodiversity, biomass, and ecosystem functioning. Bryology is the discipline that studies bryophytes, including ethnobryology, which focuses on the traditional uses of these organisms. Methods: This study presents information on the use of bryophytes in Ecuador. A systematic review was conducted using local, regional, and global databases covering the period 1990–2025, following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Results: A total of 107 articles were identified, of which 88 were indexed in global database (Scopus and Web of Science), one in SciELO, six in Latindex, two book chapters from Springer and eleven in other indexing databases. Number of articles did not follow a consistent pattern, with few studies in the early years and several years with no publications; however, from 2008 onward, the number of studies increased, ranging from two to peaks of nine publications per year. Most research focused on ecological topics, followed by taxonomic, phytochemical, and molecular studies, whereas no studies addressed ethnobryology. A total of 82 studies focused exclusively on bryophytes, 22 combined bryophytes and lichens, and three addressed biological soil crusts. Epiphytic bryophytes were the most frequently studied group (39 studies), followed by terricolous species (29 studies). For the first time in Ecuador, a list of 28 bryophyte species was compiled from an ethnobryological perspective. Conclusions: Although bryological research has increased in recent years, fields such as ethnobryology, phytochemistry, molecular studies, and biological soil crust research remain underexplored and require further investigation. Thus, this study provides the first documented record in Ecuador of the uses of 28 bryophyte species. Keywords: Ethnobryology; bryophytes; epiphytes; PRISMA; Scopus